ANALISIS HASIL INTERPRETASI JAWABAN MATEMATIKA SISWA PADA PEMBELAJARAN MATEMATIKA - Nelpiani Simatupang; Roslian Lubis; Sinar Depi Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
The aim of the research is to analyze the results of the interpretation of students' mathematical answers in mathematics learning in SMA Negeri 1 Andam Dewi. The approach of the research is descriptive qualitative. Subject of the research consist of 13 students. Observation, test, and interview were used in collecting the data and triangulation technique was used in analysis technique. The research of the research shows the average of the interpretation of students' mathematical answers in mathematics learning is 75.59 ( medium category). It’s concluded the interpretation of students' mathematical answers in mathematics learning in SMA Negeri 1 Andam Dewi include students able to find information or problems, compare the relevance of information or problems, analyze, check back and draw conclusions.